Flexible Work Arrangements and Workplace Productivity: Examining The Nexus - Njideka Phina Onyekwelu; Ezieshi Francis Monyei; Uju Sussan Muogbo (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study investigates the nexus between flexible working arrangements (FWA) and the productivity of the selected workplaces across the 6 geo-political zones in Nigeria. Research methodology: The descriptive survey design was used, with a population of 600 businesses in chosen states throughout Nigeria's six geopolitical zones. Using the statistical procedure developed by Krejcie and Morgan (1970), a sample size of 234 was found. Data was acquired from primary sources, and descriptive (mean) and inferential statistics were used to analyze the data with a 5% level of significance. Results: Flexible work arrangements had a positive statistical effect on workplace productivity (R2 = 0.882359, F = 1545.089, p-value = 0.05). Limitations: One state does not efficiently represent the geopolitical zones. Contribution: FWA can influence the development of business policies and strategies as revealed in the study. As such, businesses must adapt and invest in strategies that support and facilitate FWA such as information and technology systems, as they have become crucial to both staff and workplace viability.